Plasma pharmacokinetics and urinary excretion of tenofovir following cessation in adults with controlled levels of adherence to tenofovir disoproxil fumarate - Tim R. Cressey (2020)
© 2020 The Authors Objectives: The aim was to fully characterize the plasma and urine washout pharmacokinetics of tenofovir (TFV) in adults following 6 weeks of controlled levels of tenofovir disoproxil fumarate (TDF) adherence, in order to inform the utility of clinic-based adherence testing. Design: This was a three-arm, randomized, open-label study in adult volunteers. Participants were randomized to receive TDF 300 mg/emtricitabine (FTC) 200 mg as (1) 7 doses/week (perfect adherence), (2) 4 doses/week (moderate adherence), or (3) 2 doses/week (low adherence). Plasma and urine samples were collected regularly during the 6-week dosing phase and for 4 weeks following drug cessation. Results: Twenty-eight adults were included in this analysis. Median (range) age was 33 (20–49) years. No differences in TFV pharmacokinetic parameters during the washout were observed across the study arms. Small differences in TFV plasma concentrations occurred across arms between 4 and 10 h post-dose. The cumulative amount of TFV excreted in urine was not different at 24 h post-dose, but at 148 h it was 24.8 mg, 21.0 mg, and 17.2 mg for the perfect, moderate, and low adherence arms, respectively (p = 0.043). Conclusions: Among adults with different TDF adherence patterns, relative differences in plasma concentrations and cumulative urine extraction of TFV were minor following cessation. TFV measurement in plasma or urine is more indicative of last drug ingestion, rather than prior dose patterns.